Optimization Analysis of Advanced Support for Thick and Hard Roof - Zhang, Yongkun; Wang, Kaiwei (International Journal of Natural Resources and Environmental Studies, 2025)
Based on the geological conditions of 1033 working face in Yuandian No.1 Coal Mine, this paper studies the support distance and support strength of hydraulic support in the advanced section of roadway roof. Through numerical simulation analysis, the advance support range of the advance roadway is 5m, 10m, 15m, 20m and 25m four kinds of distance plastic zone and stress cloud diagram; at the same time, in-depth analysis of 0.4 MPa, 0.8 MPa, 1.2 MPa and 1.6 MPa of these five different advanced hydraulic support support strength. Through the above research, it is concluded that the advance support distance of the working face is more suitable at 20 m, and the advance support strength is in the range of 0.8 MPa 1.2 MPa.